Analysis Internal Control System for Management of Merchandise Inventory in PT. Fuji Kinzoku Indonesia - Andreansyah, Amir; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (Westscience Press, 2024)
An internal control system is needed to ensure that goods are in the warehouse to be sent to consumers. Inventory control should be able to present more accurate information to management so that it can help as a decision-making process. If the inventory control technique is effective and efficient enough, it is necessary to pay attention to the information and data of the company's inventory control system. This study aims to determine how the internal control system of trade goods inventory of PT Fuji kinzoku Indonesia works. This research applies a qualitative descriptive method approach. To obtain this data, researchers conducted interviews with production employees, logistics, and logistics leaders of PT Fuji Kinzoku Indonesia. The analysis technique in this research is through data collection, then data presentation, data analysis, and then drawing conclusions. The results showed that the problems that occur in the inventory of trade goods are caused by machine trouble so that inventory for shipping is problematic. To overcome this problem, PT Fuji Kinzoku Indonesia holds inventory stock for several shipments so that the shipping process continues to run smoothly. So that the internal control system of inventory shows that the analysis of the internal control system for managing the stock of trade goods of PT Fuji Kinzoku Indonesia has been running effectively. The results of this study indicate that the environmental control component is adequate, risk assessment is adequate, control activities are adequate, information and communication are adequate, and monitoring has been carried out adequately.